GIGANTIC ADRENAL CYST MIMICKING MESENTERIAL TUMOR: A CASE REPORT (Indonesian Journal of Urology, 2022)
Objective: This study aims to know the effects of giant adrenal cysts and their challenges for surgeons. Case(s) Presentation: A 41 years old female was referred with a chief complaint of growing palpable mass on the left side of the abdomen since five months ago. During the past five months, the patient has also had complaints of hard narrow-caliber stools. The general conditions and vital signs have been within normal limits. Discussion: Complete resection of the tissue remains the current best treatment of choice. When available, laparoscopic adrenalectomy is the gold standard for treating giant adrenal cysts. Open adrenalectomy is an alternative when laparoscopic adrenalectomy is not available, or when there is not enough diagnostic information preoperatively. For large cysts with a size of >6cm, open surgery is the favorable treatment, because it is difficult to control the mass via the laparoscopic approach. Conclusion: The giant adrenal cyst is a rare condition that, due to its size, it could lead to moderate-severe abdominal symptoms. Localizing the origin of the cysts preoperatively poses a challenge for surgeons and diagnosticians. Intraoperative diagnostic and therapeutic with laparoscopy or open surgery is recommended for these cases.